Family caregivers’ needs of people with orphan diseases: closing arrows through nursing care - Martínez Reyes, Cielo (2020)
Objective: establish the needs of family caregivers of people with orphan diseases considering the Adventist Nursing Model. Methodology: Literature review covering quantitative and qualitative articles found in databases and journals indexed in Spanish, English and Portuguese languages, between 2014 and 2019, whose methodological rigor met STROBE, COREQ, PRISMA, and JADAD criteria. The information obtained was related to the Adventist Nursing Model, NOC, and NIC. Results: 28 articles were selected that analyzed physical, psychological, social, educational, spiritual, health care and economic needs in caregivers of people with orphan diseases, which required multidisciplinary and integral support, including nurse spiritual support through interventions proposed by the NIC, and the Adventist Nursing model (care, connection with God and the other, and empowerment of the caregiver in their own health). Conclusion: the needs of caregivers cover different areas of being, which can be approached independently and interdependently, identified by theoretical models.